Erratum :Gradient auto-tuned Takagi-Sugeno Fuzzy Forward control of a HVAC system using predicted mean vote index (Energy and Buildings (2012) 49 (254-267)) - Homod R.Z.; Sahari K.S.M.; Almurib H.A.F.; Hafiz Nagi F. (Elsevier Ltd, 2023)
[No abstract available]